If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + -4 + 2x = 21 Reorder the terms: -4 + 3x + 2x = 21 Combine like terms: 3x + 2x = 5x -4 + 5x = 21 Solving -4 + 5x = 21 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '4' to each side of the equation. -4 + 4 + 5x = 21 + 4 Combine like terms: -4 + 4 = 0 0 + 5x = 21 + 4 5x = 21 + 4 Combine like terms: 21 + 4 = 25 5x = 25 Divide each side by '5'. x = 5 Simplifying x = 5
| (1-4a)(1-9a)= | | -3(X+4)=-8X | | 2y-2x=14 | | x^2+2x-63= | | -6(-6k+7)-8k=70 | | x*x-x=.3125 | | a+25=18 | | 4m-5=15 | | 3(6)-5=y | | -3(x+3)-5(1+7x)=62 | | 3c+12=-7 | | x+2+3x-4+5=15 | | x+4.3=-2.7 | | 2a+13=21 | | -60=-6(-8x+2) | | 4r^2-23r-6=0 | | 4(6)-y=7 | | x+2+3x-4=15 | | -0.08x=0.56 | | 3x+9=6x+2 | | 8.75+1.25=15.00 | | 6k^2-2k=0 | | 2t=2(t+5) | | 8.75-1.25=15.00 | | X+29+5x-3-4X=X+44 | | Lnx+ln(x+2)=3 | | 5x+2y=-2 | | -2(3b-4)+6(1+2b)=-4 | | 3(1+8x)+7x=65 | | 4m+12=8 | | 7(1+8n)+7(n+6)=49 | | -4x=x-(4x) |